Problématique pour une meilleure gestion Du Mul Tilinguisme social de type Afro-Européen en Afrique au Sud du Sahara - Baka, Jean (Afrika Focus, 2005)
Generally two types of multilingualism are distinguished: individual multilingualism and social multilingualism. This paper has a double aim: 1. The analysis of the solutions designed for the management of social multilingualism in general and afro-european multilingualism in particular. 2. The proposal of a language policy approach, which takes into account ethnic differences, cultural particularities and the importance of languages of mass communication. This approach will allow democratise the education system by an augmentation of school attendance rates, the limitation of failures and school desertion and annihilation of illiteracy and niral exodus. The approach offered is exemplified by the case of Republic of Congo. Key Words: Multilinguialsm, Congo-Brazzaville, Language Policy, Language Education, Indigenous Development, Sub-Sahara Africa.